2020
DOI: 10.1002/cphc.201901070
|View full text |Cite
|
Sign up to set email alerts
|

Evolutionary Algorithm‐based Crystal Structure Prediction for Gold(I) Fluoride

Abstract: Solid gold(I) fluoride remains as an unsynthesized and uncharacterized compound. We have performed a search for potential gold(I) fluoride crystal structures using USPEX evolutionary algorithm and dispersion‐corrected hybrid density functional methods. Over 4000 AuF crystal structures have been investigated. Behavior of the AuF crystal structures under pressure was studied up to 25 GPa, and we also evaluated the thermodynamic stability of the hypothetical AuF crystal structures with respect to AuF3, AuF5, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 71 publications
1
10
0
Order By: Relevance
“…Finally, a trigonal structure ( R 3, V =1368 Å 3 , Z =12, i. e. 4 formula units in the primitive cell) also showed a relatively low energy difference of 5.3 kJ/mol per formula unit compared to the cubic CaTiF 6 ‐type structure. The USPEX structural searches up to 8 formula units in primitive cell failed to produce any low‐energy structures and resulted in low‐symmetry structures, in line with our previous experiences with the same structure prediction methodology [62,63] . Therefore, we did not investigate any compositions with more than 8 formula units in the primitive cell.…”
Section: Resultssupporting
confidence: 54%
“…Finally, a trigonal structure ( R 3, V =1368 Å 3 , Z =12, i. e. 4 formula units in the primitive cell) also showed a relatively low energy difference of 5.3 kJ/mol per formula unit compared to the cubic CaTiF 6 ‐type structure. The USPEX structural searches up to 8 formula units in primitive cell failed to produce any low‐energy structures and resulted in low‐symmetry structures, in line with our previous experiences with the same structure prediction methodology [62,63] . Therefore, we did not investigate any compositions with more than 8 formula units in the primitive cell.…”
Section: Resultssupporting
confidence: 54%
“…We start with two fluoridest hat were studied experimentally at high pressure:A gF and AgF 2 .F or the latter compound, diamonda nvil cell (DAC) experiments indicated that the distorted HP-PdF 2 -type structure (space group Pbca, Z = 4) transforms to as tructure with Pca2 1 (Z = 4) symmetry at 10 GPa, which in turn transforms to ad istorted HS-ZrO 2 -type [33] phase (Pbcn symmetry, Z = 8) at 15 GPa. [19] Our calculations reproduce thisp hase sequence, with the phase transition pressures underestimated by 4GPa (Pbca 6 GPa ! Pca2 1…”
Section: Resultsmentioning
confidence: 63%
“…The reactivity of elemental fluorine at pressures exceeding 1GPa (= 10 kbar) has recentlya ttracted increased scientific attention because of the exotic nature of materials that are predicted to form in fluorine-richs ystems at large compression. [1][2][3][4][5][6][7][8][9][10][11][12][13][14] These include compounds featuring elements in high oxidation states (e.g.,I F 8 ), [13] hypervalent second-rowe lements (NF 5 ), [8] as well as transients pecies that are not attainable at ambient conditions (AuF 2 , [3,4] AuF [6] ). In the case of transition metal fluorides, this novel chemistry might lead to species featuring exotic magnetic ions, such as Au 4 + (5d 7 electronic configuration) or Au 2 + (5d 9 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…8 With the exception of AuF, all other gold(I) halides are known in the condensed state. 1 , 9 The molecular AuF was characterized in the gas phase. 10 In the solid state, it was stabilized by an N-heterocyclic carbene ligand.…”
Section: Introductionmentioning
confidence: 99%